-1/8n = 16 - 5
-1/8n = 11
-n = 88
n = -88
2006-12-10 14:46:40
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
Begin by subtracting 5 from the right side to get:
-1/8n=11
then multiply both sides by 8 to get:
-n=88
so n=-88
2006-12-10 14:49:59
·
answer #2
·
answered by Mike 3
·
0⤊
0⤋
Clear the fraction by multiplying the equation by 8:
8[5 - (1/8)n] = 8*16
40 - n = 128
- n = 128 - 40 =88
n = - 88.
2006-12-10 14:48:31
·
answer #3
·
answered by S. B. 6
·
0⤊
0⤋
5- 1/8n =16 subtract 5 from each side
-1/8 n=11 multiply both sides be -8
n=-88
2006-12-10 14:47:27
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
-1/8n = 11, substract 5 from both sides
-1/n = 11(8) = 88, multiply 8 to both sides
n = -1/88
2006-12-10 14:49:12
·
answer #5
·
answered by asndude7 2
·
0⤊
0⤋
first subtract 5 on both sides
then u get -1/8n = 11
then u divide -1/8 on both sides
u get n by itself , and n wud equal to 11/(-1/8) = -88
n = -88
2006-12-10 14:47:34
·
answer #6
·
answered by Holymasteric 3
·
0⤊
0⤋
To do this first subtract the 5 on both sides, then multiply by the reciprocal of the fraction (it's -8) to both sides.
You should get -88.
2006-12-10 14:48:33
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
i hope n isnt in the denominator.
5-(1/8)n=16
5-16= (1/8)n
-11=-(1/8)n
n= -88
if its like this, 5-1/8n=16,(n in denominator)
then,
-11=1/8n
8n=-1/11
n= -1/88
just see what u want..
hope u r satisfied.
2006-12-10 14:50:52
·
answer #8
·
answered by For peace 3
·
0⤊
0⤋
first you have to subtract the 5 from both sides to get
-1/8n=11
then divide -1/8 by both sides to get n=(-1/8)/11 i dunno i dont have a calculator
2006-12-10 14:49:09
·
answer #9
·
answered by ? 5
·
0⤊
0⤋
(3)/(4)+(one million)/(3)*x=(2)/(4) Multiply (one million)/(3) by using x to get (x)/(3). (3)/(4)+(x)/(3)=(2)/(4) cut back the expression (2)/(4) by using removing a element of two from the numerator and denominator. (x)/(3)+(3)/(4)=(one million)/(2) because of the fact that (3)/(4) does not incorporate the variable to resolve for, pass it to the dazzling-hand edge of the equation by using subtracting (3)/(4) from the two aspects. (x)/(3)=-(3)/(4)+(one million)/(2) Simplify the dazzling-hand edge of the equation. (x)/(3)=-(one million)/(4) Multiply each and each term interior the equation by using three. (x)/(3)*3=-(one million)/(4)*3 Simplify the left-hand edge of the equation by using canceling the person-friendly words. x=-(one million)/(4)*3 Multiply -(one million)/(4) by using three to get -(3)/(4). x=-(3)/(4)
2016-10-18 02:22:10
·
answer #10
·
answered by ? 4
·
0⤊
0⤋